2016
DOI: 10.1002/ijc.29987
|View full text |Cite
|
Sign up to set email alerts
|

Proportion of premenopausal and postmenopausal breast cancers attributable to known risk factors: Estimates from the E3N‐EPIC cohort

Abstract: Breast cancer is the most frequently diagnosed cancer among women worldwide. Breast cancer risk factors have been widely explored individually; however, little is known about their combined impact. We included 67,634 women from the French E3N prospective cohort, aged 42-72 at baseline. During a 15-year follow-up period, 497 premenopausal and 3,138 postmenopausal invasive breast cancer cases were diagnosed. Population-attributable fractions (PAFs) were used to estimate cases proportions attributable to risk fac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
43
0
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 47 publications
(50 citation statements)
references
References 51 publications
4
43
0
3
Order By: Relevance
“…This estimate was close to those obtained at the end of follow-up with the nonparametric methods and at the start of follow-up with the parametric and semiparametric approaches. In a recent publication, Dartois et al [12] reported a higher AR estimate of 14.5% (95% CI, 9.2 to 19.6%) for recent MHT use and postmenopausal invasive breast cancer from the E3N cohort data, using the approach proposed by Spiegelman et al [10] and a more refined, adjusted analysis with MHT exposure as a time-dependent covariate.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This estimate was close to those obtained at the end of follow-up with the nonparametric methods and at the start of follow-up with the parametric and semiparametric approaches. In a recent publication, Dartois et al [12] reported a higher AR estimate of 14.5% (95% CI, 9.2 to 19.6%) for recent MHT use and postmenopausal invasive breast cancer from the E3N cohort data, using the approach proposed by Spiegelman et al [10] and a more refined, adjusted analysis with MHT exposure as a time-dependent covariate.…”
Section: Discussionmentioning
confidence: 99%
“…By June 2008 (for a maximal 16.4 years and mean 14.0 years of follow-up), 2,228 invasive breast cancers had been diagnosed (1, 106 in unexposed women). A recent work on the E3N cohort estimated a 14.5% postmenopausal breast cancer risk attributable to MHT use after 15 years of follow-up [12]. We estimated AR as a CDF-based function of time at four time points using nonparametric, semiparametric and parametric approaches, as well as the single overall AR measure proposed by Spiegelman et al [10].…”
Section: Introductionmentioning
confidence: 99%
“…Modifiable risk factors for breast cancer that could be addressed in a smartphone app for preventing breast cancer in women are shown in (Table 1). Based upon attributable risks, about 30–35% of breast cancers could potentially be prevented by addressing obesity, physical inactivity, alcohol consumption, and HRT (29,30). …”
Section: Modifiable Risk Factors For Breast Cancermentioning
confidence: 99%
“…The burden of breast cancer preventable by modifications to certain causally related risk factors can be quantified by calculating population attributable fractions (PAFs). Only one cohort study has evaluated the individual and joint contributions of modifiable risk factors on the breast cancer burden for premenopausal women, and several have examined the breast cancer burden for postmenopausal women. All previous studies evaluated the complete removal of the exposure, even though a gradual reduction in exposure might be more realistic.…”
Section: Introductionmentioning
confidence: 99%